Penerapan Media Gambar Ilustrasi Untuk Meningkatkan Prestasi Belajar Siswa Dalam Menanggapi Cerita Yang Didengar Kelas IV SD 29 Saok Laweh - Mida, Dewi Putri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to describe the use of illustrated visual aids in improving students' skills in responding to stories. This research is a quantitative research using Kurt Lewin’s PTK model which includes planning, action, observation, and reflection. With illustrated visual aids, it is easier for students to accept learning concepts and can attract students' interest to actively participate in the learning process. From the results of the formative test of early learning the average value which was originally only 6.8 increased to 7.2 in the first cycle, while in the second cycle it increased to 79 while the learning completeness from the initial learning which was only 40% increased to 60% in the first cycle, while in the second cycle it increased to 80%. Through increasing the average score of formative test results, and student learning completeness. So the understanding of Indonesian class IV about retelling the contents of folk tales that are read or heard in a coherent and complete way can be improved using the "illustration image" props.